Influence of the initial moist curing time on the sulfate attack resistance of concretes with different binders. (30th July 2017) - Zhang, Zengqi; Wang, Qiang; Chen, Honghui; Zhou, Yuqi
Highlights: GGBS enhances the sulfate attack resistance of concrete even under insufficient moist curing condition. Moist curing for at least 7 days is necessary for the concrete containing fly ash. The sulfate attack resistance of concrete is less sensitive to the moist curing time at lower W/B ratio. Abstract: The influence of the initial moist curing time on the resistance to the sulfate attack of concretes with different binders and at different water/binder ratios was studied by determining the compressive strength and the chloride ion permeability of the concrete before sulfate attack, the compressive strength after sulfate attack, and the microstructure of the corroded concrete matrix. The results illustrate that both the crystallized sodium sulfate and ettringite formed due to invaded sulfate are the principal expansion sources of the concrete subjected to the sulfate attack environment. Both the additions of fly ash and ground granulated blast furnace slag (GGBS) tend to significantly reduce the permeability and enhance the sulfate attack resistance of concrete on the premise of sufficient moist curing. The enhancing effect of GGBS is greater than that of fly ash on the sulfate attack resistance of concrete with each initial moist curing regime. In the case of insufficient moist curing for 3 or 7 days, the compressive strength loss rate of concrete containing fly ash is close to that of the plain cement concrete, indicating that the addition of fly ash makes little contribution to the enhancement of the sulfate attack resistance of concrete. Though the enhancing effect of GGBS on the sulfate attack resistance of concrete decreases with the decrease of moist curing time, the compressive strength loss rate of the concrete containing GGBS is about half of that of the plain cement concrete. The sulfate attack resistance of concrete is less sensitive to the moist curing time at lower water/binder ratio.